2017
DOI: 10.6106/jcepm.2017.3.30.001
|View full text |Cite
|
Sign up to set email alerts
|

Construction Delays in Developing Countries: A Review

Abstract: Construction delay is one of the basic constrains to achieve the project objectives in developing countries. This study aims to find the causes and effects of construction delays in developing countries. A thorough literature review has been done following the content analysis method. The relevant literature of 28 developing countries was collected from the scholarly journals published in the period of 2006 to 2016. The different developing countries are grouped into three geographic regions, i.e. South and So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 45 publications
2
16
1
3
Order By: Relevance
“…From the review of literature, it is found that nature of delay causes in developing countries is significantly different from that in developed countries. In the case of developing countries, delay causes are originating internally from contractor or client, such as financial difficulties, cash flow problems, change orders by client and payment delays by owner (Islam and Trigunarsyah, 2017). In the case of developed countries, external causes such as weather, prices of materials, permits and labor supply are critical causes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the review of literature, it is found that nature of delay causes in developing countries is significantly different from that in developed countries. In the case of developing countries, delay causes are originating internally from contractor or client, such as financial difficulties, cash flow problems, change orders by client and payment delays by owner (Islam and Trigunarsyah, 2017). In the case of developed countries, external causes such as weather, prices of materials, permits and labor supply are critical causes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prasad et al (2019) revealed that payment delays in developed countries are caused mainly due to external factors, such as weather, material prices, permits and labour supply. According to Islam and Trigunarsyah (2017), in developing countries, delayed payments are caused by contractors or clients because of financial difficulties, cash flow issues and variation orders. Bureaucracy in Government entities also causes significant delays in the payments made to the contractors (Niazi and Painting, 2017).…”
Section: Literature Review 21 Management Of Delayed Payments In Government Building Construction Projects By Partiesmentioning
confidence: 99%
“…The findings reveal that road projects are prone to cost overruns, they have a very large magnitude of cost overruns and the causes of cost overruns vary for all road projects (Ahmad, Anigbogu, & Molwus, 2018). Islam and Trigunarsyah (2017) identify the main reason for the delay as financial issues like; contractor's cash flow problem, and delay in progress payment by the employer, managerial issues such as poor site management, contractor related factors, i.e., improper planning and scheduling, and employer-related factor-like order for design change during construction is the most important and frequent factor that directly forces to delay the work schedule all over the developing world. The delay and cost overrun of infrastructure projects were caused by 20 factors according to the records in the collected final reports of projects.…”
Section: Literature Reviewmentioning
confidence: 99%